Ambrogio Traversari – „pokrytec“ pod Sluncem Bernardina Sienského? - Jan Stejskal (Theatrum Historiae)
The subject of the text is a dispute between humanism in the early Renaissance and the Franciscan Observance. The contradiction is demonstrated on the example of the ambivalent relationship between Ambrogio Traversari (humanist, translator from Greek) and Bernardino of Siena. Contemporary debate about the popular worship of the name of Jesus, the scope of which was evident even in our country, is discussed in detail.